Advancing Solar Panel Energy Efficiency for Space Exploration: Leveraging Multi - Junction Technologies, Radiation Resistance, AI - Based Tracking, and Dust Mitigation Strategies - Gupta, Saurabh (Journal of Research in Science and Engineering, 2025)
This study explores innovative strategies to enhance solar panel energy efficiency in space exploration. It examines the integration of multi - junction solar cells, radiation - resistant materials, AI - driven solar tracking systems, and advanced dust mitigation methods. Using a multidisciplinary approach, the research highlights potential efficiency improvements of up to 25%, addressing key challenges such as radiation degradation and dust accumulation. These findings pave the way for the next generation of robust and efficient solar technologies, critical for sustaining space missions.